XPS investigations of VPO catalysts under reaction conditions - Kleimenov E.; Bluhm H.; Hävecker M.; Knop-Gericke A.; Pestryakov A. N. Aleksey Nikolaevich; Teschner D.; Lopez-Sanchez J. A.; Bartley J. K.; Hutchings G. J.; Schlögl R. (2005, 2005)
The surface of vanadium phosphorus oxide (VPO) catalysts was investigated by (in situ) X-ray photoelectron spectroscopy (XPS) under reaction conditions. Two differently prepared VPO samples with similar catalytic activities showed different spectral behaviour while the catalytic conditions were changed. The vanadium surface oxidation state of both catalysts was found to have the same value close to 4 under reaction conditions while the oxidation state of vanadium in deeper layers differed significantly. The experimental results suggest that in VPO the catalytically active species located in the topmost surface layers (up to 1 nm depth) are only weakly related to the structure of deeper layers. Based on our results we suggest that the deeper layers act as a substrate material only and can be different from the surface.